Experimental investigations of wearable antenna on flexible perforated plastic substrate. Issue 2 (February 2017) - Kumar, Raghvendra; Kumar, Pankaj; Gupta, Nisha; Dubey, Rahul
ABSTRACT: In this article, the performance of a rectangular patch antenna on inexpensive perforated flexible plastic substrate is investigated experimentally. The antenna is designed for wearable application operating at Wi‐Fi and HiperLAN frequency bands. The regular perforations in the substrate material help in reducing the dielectric losses which is common with other textile materials thus improving the antenna performance. The prototype model of the proposed antenna is developed and measured. Various parameters such as return loss, VSWR, radiation pattern and gain are presented to validate the suitability for wearable applications. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:265–270, 2017